The Role of the Principal as Leader, Manager, and Motivator in Developing and Improving Extracurricular Activities at SMK Asy Syarifiy - Sholihah, Arifatus; Turmudi, Imam; Sukamto, Sukamto (SAINTIS Publishing, 2025)
This study aims to describe the role of the principal in developing extracurricular activities at SMK Asy Syarifiy. In addition, to find out how the principal as a Leader in improving extracurricular activities at SMK Asy Syarifiy, how the principal as a Manager in improving extracurricular activities at SMK Asy Syarifiy, and how the principal as a Motivator in improving extracurricular activities at SMK Asy Syarifiy. This study uses a qualitative approach, which is implemented at SMK Asy Syarifiy using a case study design. Data collection techniques used include (1) In-depth interviews, (2) Observation (3) Documentation. Informants are selected using purposive sampling. Data collected through these techniques are organized, interpreted and analyzed in the form of checking data credibility with triangulation procedures, data verification/cross checks, and checking the adequacy of references. While dependability and confirmability are achieved through audits by supervisors. The results of the study revealed that: (1) The role of the principal as a leader in improving extracurricular activities at SMK Asy Syarifiy is to provide the facilities and infrastructure needed for extracurricular activities. (2) The role of the principal as a motivator in improving extracurricular activities at SMK Asy Syarifiy is to provide motivation in the form of something that is a reward for them, provide encouragement and guidance and direction to students.